Lean TPM : a blueprint for change - McCarthy, Dennis
Deals with the chemical and physical properties of cements and concretes and their relation to the practical problems that arise in manufacture and use. Much attention is given to the suitability of materials, to the conditions under which concrete can excel and those where it may deteriorate and to the precautionary measures that can be adopted.